In-Silico Analysis for cryI Gene Amplification from Bacillus thuringiensis - Febriana Dwi Wahyuni; Henny Saraswati; Kartika Sari Dewi (BIOEDUKASI, 2020)
Abstract Bacillus thuringiensis is one type of bacteria that has been used as a microbiological control agent for pests and a vector of plant disease. The presence of Cry proteins inside the B. thuringiensis can be acted as a specific insect repellent that only toxic to certain insects. The CryI protein is toxic to Lepidoptera insects which can attack various types of plants. Polymerase Chain Reaction (PCR) is a common method that can be used to amplify the gene encoding CryI proteins from B. thuringiensis. This research aimed to design a good primer candidate for cryI gene amplification from B. thuringiensis. In silico analysis for designing cryI primer was carried out using some software, such as BLAST for searching cryI gene sequence, Bioedit for sequences alignment, and DINAmelt for analyzing dimer structure of primers. Ten primer candidates were successfully obtained based on the result of the primer3 software. A pair of primer was selected to amplify the cryI gene, with forward primer 5’- CGGTGAATGCCCTGTTTACT -3’ and reverse primer 5’-CGGTCTGGTTGCCTATTGAT -3’. Amplification of the cryI gene by PCR method using selected primer resulting in a PCR product with a length of approximately 200 bp.